Markers of renal disease and function are associated with systemic inflammation in HIV infection1. Issue 10 (20th May 2015) - Gupta, SK; Kitch, D; Tierney, C; Melbourne, K; Ha, B; McComsey, GA; AIDS Clinical Trials Group Study A5224s Team
<x xml:space="preserve">Abstract</x> Objectives Both renal disease and systemic inflammation predict non‐AIDS‐defining events and overall mortality in HIV‐infected patients. Here, we sought to determine the relationships between renal disease and circulating inflammation markers. Methods We performed a secondary analysis of AIDS Clinical Trials Group Study A5224s to determine if markers of renal disease [urine protein:creatinine ratio (uPCR), urine albumin:creatinine ratio (uACR), and estimated glomerular filtration rate (eGFR), using Chronic Kidney Disease Epidemiology Collaboration (CKD‐EPI) creatinine and cystatin C‐creatinine] were associated with markers of systemic inflammation [high‐sensitivity C‐reactive protein, interleukin‐6, tumour necrosis factor (TNF)‐α, soluble TNF‐α receptor I (sTNFRI), sTNFRII, and soluble vascular cellular and intercellular adhesion molecules]. We correlated these renal and inflammatory markers prior to antiretroviral initiation and after 96 weeks of therapy. Results We found that eGFR (estimated using CKD‐EPI cystatin C‐creatinine), uPCR, and uACR were significantly correlated with most assessed markers of systemic inflammation prior to antiretroviral initiation. uPCR and eGFR (using CKD‐EPI cystatin C‐creatinine), but not uACR, remained significantly correlated with most of the assessed inflammatory markers after 96 weeks of antiretroviral therapy (ART). Most of these correlations, although statistically significant, were < 0.50. eGFR using CKD‐EPI creatinine was much less frequently associated with inflammation markers and only significantly correlated with sTNFR1 at week 0 and with sTNFRI and II at week 96. Conclusions Renal disease and function were associated with systemic inflammation in HIV infection, both before and after ART. Systemic inflammation may partially explain the relationships between proteinuria, albuminuria, and reduced renal function and future adverse outcomes.